OPTIMASI PENJADWALAN PERKULIAHAN MENGGUNAKAN METODEAUTO GENERATE TIMETABLE DENGAN ARRAY - Hani Dewi Ariessanti; Dwi Sloria Suharti; Ary Budi Warsito (CCIT Journal, 2018)
Scheduling is one of the many problems that has been done in research for many years. Problems preparing the schedule in college are about college scheduling. The timing process should be done for each semester, which is a tiring and time-consuming task. The overall allocation of events in timeslots and spaces is done by the course scheduling process by considering the list of hard constraints and soft constraints, so there is no conflict created in allocating the schedule. Therefore, it is necessary to create a lecture scheduling application that is able to facilitate and overcome the problems in organizing the lecture schedule. The proposed scheduling system design proposed in this study is to optimize the schedule of lectures using the Auto Generate Timetable method with arrays to find the best candidates for college scheduling with the aim of minimizing the conflict and optimizing the scheduling schedule. This method is based on the process of lecturing process that has been conducted in college. Every curriculum, space, day / time, is needed to arrange the schedule of students and lecturers as part of the scheduling variable that is the solution candidate. Then the process of adjusting to constraints has been made with various parameters. The research method is to collect the data, analysis, design, coding, testing and up to the maintenance phase by using the Waterfall System Development Lifecycle method. The waterfall model provides a life-cycle approach to the development of software systems in sequential or sequential form. So with the existence of this application, it is hoped that the arrangement of lectures will not find problems as a constraint in arranging the lecture schedule